Effect and mechanism of Nintedanib on acute and chronic radiation-induced lung injury in mice - Kun Zhang; Lu Ren; Yujie Zhai (PLoS ONE, 2025)
Objective To investigate the efficacy of Nintedanib in treating acute and chronic radiation-induced lung injury and its mechanism of action. Methods A radiation-induced lung injury model was established in mice using 6MV X-rays at 18Gy to irradiate the lungs. The mice were randomly divided into four groups: control group, radiation therapy group, low-dosage Nintedanib + radiation therapy group, and high dosage Nintedanib + radiation therapy group. The mice were euthanized on day 14 and 3 months post-radiation to observe changes in acute and chronic inflammation and the expression of related proteins. Results Compared to the radiation therapy group, the low and high-dosage Nintedanib groups showed varying degrees of improvement in mental state, responsiveness, food and water intake, and fur condition. During the acute inflammatory phase, HE staining revealed inflammatory changes in the lung tissues of both Nintedanib groups, but the pathology was less severe than in the radiation group, with the high-dosage group showing more significant reduction. Serum levels of IL-6, TNF-α and TGF-β1 were significantly reduced (P < 0.05), suggesting that Nintedanib can decrease the expression of serum inflammatory factors. The percentage of Smad2-positive area in the low and high-dosage Nintedanib groups was (7.395 ± 0.90)% and (5.577 ± 1.56)%, respectively, both significantly lower than the radiation group (P < 0.05). At 3 months post-radiation, Masson’s trichrome staining showed that the Ashcroft score in the Nintedanib groups was significantly lower than in the radiation group (P < 0.05). There were statistically significant differences between the low and high-dosage groups in the percentage of Smad2 and αSMA-positive areas and the levels of serum TGF-β1 (all P < 0.05), and both were significantly lower compared to the radiation group (P < 0.05). Conclusion (1) Nintedanib can improve the general condition of mice with acute and chronic radiation-induced lung injury and reduce pathological damage to lung tissue. (2) Nintedanib may exert a protective effect on mice with acute and chronic radiation-induced lung injury by downregulating the TGF-β1/Smad2 signaling pathway, thereby inhibiting inflammatory and fibrotic responses.